2022
DOI: 10.3390/jpm12020254
|View full text |Cite
|
Sign up to set email alerts
|

Do the Mandibular Condyles Change Their Positions within Glenoid Fossae after Occlusal Splint Therapy Combined with Physiotherapy in Patients Diagnosed with Temporomandibular Joint Disorders? A Prospective Case Control Study

Abstract: The research question was: do the mandibular condyles change their position within glenoid fossae after treatment combining occlusal splint therapy and physiotherapy in patients diagnosed with temporomandibular disorders (TMD)? Forty patients with TMD were included into the study. They underwent initial physiotherapy, and a six-month treatment of occlusal splint therapy with physiotherapy. Cone-beam computed tomography images of temporomandibular joints (TMJs) were taken before and after the treatment. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 21 publications
6
25
0
Order By: Relevance
“…This research is part of the larger scientific project related to the changes that can be observed in patients diagnosed with TMD and treated with occlusal splint therapy combined with physiotherapy. This manuscript is the continuation and further evaluation of our recently published study, regarding the changes in the positions of the mandibular condyles within the glenoid fossae in patients diagnosed with TMD and treated with occlusal splint therapy combined with physiotherapy [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This research is part of the larger scientific project related to the changes that can be observed in patients diagnosed with TMD and treated with occlusal splint therapy combined with physiotherapy. This manuscript is the continuation and further evaluation of our recently published study, regarding the changes in the positions of the mandibular condyles within the glenoid fossae in patients diagnosed with TMD and treated with occlusal splint therapy combined with physiotherapy [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The participants were at least 18 years old and not older than 65 years old. The exclusion criteria were: rheumatic disease, history of oncology treatment, traumas in the area of head and neck, pregnancy, age below 18 years old and above 65 years old, history of previous orthodontic treatment, and lack of willingness to participate in the study [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations